Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X - Ervina, Ayu; Suharto, Yusuf; Rahmawati, Ratna (PT. Pubsains Nur Cendekia, 2023)
The critical thinking skills of class X-1 students at SMAN 3 Malang are still lacking so they need to be improved considering the importance of these skills in the 21st century. The six indicators of critical thinking that need to be improved are focus, reason, inference, situation, clarity, and overview. The purpose of this study was to determine the role of the Problem Based Learning (PBL) model assisted by problem solving padlets in improving students' critical thinking skills in class X-I. This type of research is Classroom Action Research (PTK) using the Kemmis & Mc. Taggart. Data on the average increase and completion of critical thinking skills were analyzed using quantitative descriptive. The research results showed that there was an increase in the percentage of students' critical thinking skills by 21.32% from 66.67% in cycle I to 87.99% in cycle II and an N-Gain of 0.64.